Aplikasi Channel Management dan Point of Sales pada perusahaan retail PT. XYZ dengan menggunakan metode Cross-channel dan Market Basket Analysis - Kenny Nugraha; Andreas Handojo; Alexander Setiawan (Universitas Kristen Petra, 2022)
PT XYZ is a company engaged in the retail and distribution of baby equipment located in Surabaya. Generally, the company has many stores ranging from physical stores and online stores. The problem faced at this time is that there is no system that can connect the company's internal systems including the cashier system, warehouse system, sales calculation system with the existing system in online stores such as in this case the Shopee system. To answer these problems, PT XYZ requires a website-based channel management system so that it can be integrated both on mobile and desktop. It is hoped that by using this technology, it can help companies improve the performance and sales performance of stores both physical stores and online stores. An integrated Multichannel Management System and Point of Sales Application can record every sale, stock management practically and efficiently so that when a stock transaction occurs it will always be synchronized along with transaction data from between online stores and offline stores.